A Model of Pedagogy, but is it Hegel? (Beiser, Hegel) - Moloney, Jack William (Cosmos and History: The Journal of Natural and Social Philosophy, 2007)
Book Review of: Frederick Beiser, emHegel/em, New York, Routledge, 2005, ISBN: 0415312086.br /